“Commerce according to Plato: a factor of division or political community?” - Helmer, Etienne (2022)
“Commerce according to Plato: a factor of division or political community?”. It is often thought that the Greek philosophers despise both wholesale trade between cities as retail trade within cities. According to this lengthy interpretive tradition, Plato conforms on this matter to Homeric and Hesiodic poetry: commerce has a reputation as a trade associated with dishonesty and profit-seeking, for which it is believed to promote more division and conflict than harmony and social cohesion. However, a careful reading of some passages in Plato’s Dialogues, and particularly of the Republic, reveals another aspect of his approach to commerce and its influence on the cohesion of the polis. Trying to highlight an aspect that is usually ignored by most interpreters, this paper argues that Plato sees in commerce itself a factor allowing the formation and maintenance of the community of the polis. This approach is based on Plato’s conviction that the political character of the human being is forged through multiple exchanges, among which trade plays a fundamental role.